The roles of symmetry and elongation in developing reference frames - He, Dongcheng; Ogmen, Haluk (Frontiers in Psychology, 2024)
Previous studies showed that elongation and symmetry (two ubiquitous aspects of natural stimuli) are important attributes in object perception and recognition, which in turn suggests that these geometrical factors may contribute to the selection of perceptual reference-frames. However, whether and how these attributes guide the selection of reference-frames is still poorly understood. The goal of this study was to examine systematically the roles of elongation and symmetry, as well as their combination, in the selection of reference axis and how these axes are developed for unfamiliar objects. We designed our experiments to eliminate two potential confounding factors: (i) extraneous environmental cues, such as edges of the screen, etc. (by using VR) and (ii) pre-learned cues for familiar objects and shapes (by using reinforcement learning of novel shapes). We used algorithmically generated textures with different orientations having specified levels of symmetry and elongation as the stimuli. In each trial, we presented only one stimulus and asked observers to report if the stimulus was in its original form or a flipped (mirror-image) one. Feedback was provided at the end of each trial. Based on previous studies on mental rotation, we hypothesized that the selection of a reference-frame defined by symmetry and/or elongation would be revealed by a linear relationship between reaction-times and the angular-deviation from either the most symmetrical or the most elongated orientation. Our results are consistent with this hypothesis. We found that subjects performed mental rotation to transform images to their reference axes and used the most symmetrical or elongated orientation as the reference axis when only one factor was presented, and they used a "winner-take-all" strategy when both factors were presented, with elongation being more dominant than symmetry. We discuss theoretical implications of these findings, in particular in the context of "canonical sensorimotor theory".